Directrices prácticas para la modelación conceptual de procesos del negocio - Pérez Santiago, Jennifer (Universidad Central “Marta Abreu” de Las Villas, 2014)
Large process modeling projects often require several stakeholders for the creation of process models. Modeling guidelines should guide and assist stakeholders to ensure the quality and governance of process models. This work focuses on develop a sound set of pragmatic guidelines to ensure the quality of business process models at a conceptual level. Through a controlled experiment this group of guidelines is used during the modeling of a business process. Later on, it is applied a set of quality metrics and compare the results with those obtained from a similar model that did not use guidelines. The results provide support for the use of guidelines as a way for business process modeling quality improvement; as for understanding, modification capacity and probability of the error. It was also investigated the use easiness, the utility and the intention to use them according to the model of evaluation of methods by means of a study among the students. Results reveal the "best" and "worst" guidelines as perceived by novice modelers and as the use ease has an important influence on the perceived utility, and, at the same time, both influence the novice modelers’ intention to use the guidelines.
Keywords: Calidad en la modelación de procesos de negocio; Métricas de Calidad; Comprensión; Capacidad de Modificación; Probabilidad de Error; Facilidad de Uso Percibida; Utilidad Percibida; Intención de Uso; Business Process Modeling Quality; Pragmatic Modeling Guidelines; Quality Metrics; Understanding; Capacity of Modification; Probability of Error; Perceived Easiness of Use; Perceived Utility; Intention of Use; Modelado de Procesos de Negocios; Directrices Prácticas; Evaluación de la Calidad; Gestión de Proyectos